2009
DOI: 10.1016/j.jhsa.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Pinch and Elbow Extension Restoration in People With Tetraplegia: A Systematic Review of the Literature

Abstract: Purpose We conducted a systematic review of the literature to summarize the available data on reconstructive surgeries involving pinch reconstruction and elbow extension restoration in people with tetraplegia. Methods English-language and French-language articles and abstracts published between 1966 and February 2007, identified through MEDLINE and EMBASE searches, bibliography review, and expert consultation, were reviewed for original reports of outcomes with pinch reconstruction and elbow extension restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…The current literature describing clinical outcomes mainly consists of case reports. 10 Results mainly describe functional outcomes such as muscle strength and ADL skills. 11 There are limited data about patient satisfaction, activities and participation after reconstructive surgery in persons with tetraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature describing clinical outcomes mainly consists of case reports. 10 Results mainly describe functional outcomes such as muscle strength and ADL skills. 11 There are limited data about patient satisfaction, activities and participation after reconstructive surgery in persons with tetraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Yamabe et al [4] reported the activities of daily living (ADL) of 28 patients with distal radius fracture; of 28 motions, opening a plastic bottle lid was difficult or impossible for 25/28 subjects (89%) and wringing out a rag was difficult or impossible for 20/28 subjects (71%). Thus, opening a plastic bottle lid was deemed as the most difficult motion to perform.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of these procedures are acknowledged by both surgeons and people with tetraplegia as improving function and independence with activities of daily living. 2 Experts in this field estimate that more than half of the tetraplegic population could benefit from some form of upper limb surgical procedure. 3,4 Uptake of upper limb surgery is variable and in the United States, an estimated 7% of the eligible population undergo surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it difficult for physicians and health professionals to summarize useful information from the literature for patients and even more difficult for patients to find this information for themselves. 2,7 There is a paucity of data on SCI in New Zealand (NZ) because of the lack of a national SCI register, although it seems the rate of SCI in NZ men is three times higher than in women and in men between 15 and 29 years accounting for 46% of all SCI cases. 8 Motor vehicle accidents and falls account for the majority of injuries.…”
Section: Introductionmentioning
confidence: 99%